Cancer parents' experiences of parenting concerns about minor children: A meta-synthesis of qualitative studies - Jing-Ling Li; Qin Ye; Ning Liu (Elsevier, 2024)
Background: Some cancer patients not only endure physical and mental distress due to the disease and treatment but also shoulder the responsibility of raising their children. This situation significantly impacts the patients' quality of life. While there is a growing body of qualitative research focusing on parenting concerns among cancer patients, there remains a lack of comprehensive qualitative evidence. Objective: This study aims to conduct a systematic review and synthesis of qualitative research evidence, investigating the experiences of cancer patients in raising minor children. Design: Systematic review and synthesis of qualitative studies. Setting(s): Through a screening process employing inclusion/exclusion criteria, qualitative studies specifically addressing cancer patients raising minor children were identified. Participants: Participants: A total of 669 participants from 40 studies were included in the review. Methods: Four English (Pubmed, Web of Science, Embase and Cochrane Library) and three Chinese (CNKI, Wanfang and Sinomed) databases were searched for qualitative studies of the real-life experiences of raising children in cancer patients from the establishment of the library to January 2024. The methodological quality of the included literature was assessed using the Critical Appraisal Skill Program (CSAP). Qualitative data were extracted, summarized, and meta-synthesized. Results: A total of 26 studies were included in this meta-synthesis, encompassing 11 different countries. 160 themes were extracted from these included literatures, which were combined into ten categories, ultimately forming four themes: the impact of parents' disease on their children, the challenges of parenting, coping strategies, and multifaceted parenting needs. Based on the Confidence in the Output of Qualitative research synthesis (ConQual) approach, the confidence level of the synthesized findings ranged from moderate to low. Conclusions: Cancer patients experience significant psychological stress while raising children, which can lead to a reduction in their quality of life and influence treatment decisions. These findings elucidate the parenting concerns experienced by cancer patients, allowing medical staff to understand their emotions and treatment preferences. Additionally, healthcare professionals should pay attention to the special needs of this group and develop targeted interventions to support and reduce patients' psychological stress and burden.